A study of conformal almost Ricci solitons on Kenmotsu manifolds - Sarkar, Sumanjit; Dey, Santu; Bhattacharyya, Arindam (International journal of geometric methods in modern physics, 2023)
The goal of this paper is to study conformal almost Ricci solitons within the framework of Kenmotsu manifolds. First, we demonstrate that if the potential vector field is Jacobi along the Reeb vector field, then the soliton reduces to a conformal Ricci soliton. If the manifold is η -Einstein Kenmotsu manifold, we show that either the manifold is of constant scalar curvature or the potential vector field is an infinitesimal contact transformation. In addition, if we consider the soliton vector field as a contact vector field, then either the gradient of λ is pointwise collinear with the Reeb vector field or the manifold becomes η -Einstein. Lastly, we develop an example of a conformal almost Ricci soliton on the Kenmotsu manifold.